Monitoring Hasil Perikanan dengan Alat Tangkap Pancing Tonda di Pelabuhan Perikanan Nusantara Prigi, Kabupaten Trenggalek, Propinsi Jawa Timur [Monitoring Of Fishery With Fishing Gear Troling Line In The Prigi Nusantara Fishing Port, Trenggalek District, East Java Province] - Abdul Manan; Fajar Nurcahya Dwi Putra (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Indonesia is a maritime country that has great potential of capture fisheries. There are various methods to conduct of fishing operations by fisherman, one of them is troling line. Troling line is a fishing equipment used to capture pelagic fish. The purpose of this study case is to know the technique of fishing operations by using a troling line, to find out the capture by a troling line, and to identify obstacles in the activities of fishing using a troling line. Monitoring was carried out in territory authority Prigi Nusantara Fishing Port, Watulimo, Trenggalek, East Java. This activities was held from July 19th to September 1st 2010. The method used are descriptive method with the retrieval of data includes primary data and secondary data. Data were collected by active participation, observation, and literature. Monitoring in production of troling line operation can be used to determine the effectiveness of troling line and overall process of catching up to the handling of post-catch yield. The process of fishing with the troling line respectivelly settings stage, trolling, and hauling. The kind of pelagic fish capture are Thunnus albacore, Katsuwonus pelamis, and Euthynus affinis. Total of capture is 4.556 kg. The results of this monitoring indicate that the troling line less effective in fishing operations. Barriers faced by the fishermen at PPN Prigi in conducting fishing operations is a technical problem and natural problem. Technical problem happening such as destruction of fishing gear during fishing operations.